Drug‐Delivery Systems for Tunable and Localized Drug Release. Issue 9 (23rd September 2013) - Timko, Brian P.; Kohane, Daniel S.
Abstract Drug‐delivery systems can be designed to provide localized drug release with a variety of customizable release profiles. Passive systems enable sustained, zero‐order release for days or weeks, while remotely triggered systems enable the timing and dose of drug release to be controlled by the patient or physician. Release profiles can be engineered to match the requirements of particular ailments. We review on‐demand drug‐delivery systems that release a therapeutic in response to magnetic, near‐infrared, or UV fields; such systems could extend the capabilities of sustained release systems by incorporating programmed dosing regimens.